Quantitative structural analysis of hemifacial microsomia mandibles in different age groups - Zhang, Ziwei; Chen, Xiaojun; Kim, Byeong Seop; Han, Wenqing; Yan, Yingjie; Wang, Xuetong; Li, Xin; Zhang, Yan; Chai, Gang (Frontiers in Pediatrics, 2023)
Structural analysis of mandibular asymmetry and its progression in hemifacial microsomia, especially in the body, is inconclusive. This study aims to quantitively analyze mandibular ramus and body deformities, assessing the asymmetry and progression in different components. This is a retrospective study on hemifacial microsomia children. They were divided into mild/severe groups by Pruzansky-Kaban classification and into three age groups (<1 year,1-5 years, 6-12 years old). Linear and volumetric measurements of ramus and body were collected via their preoperative imaging data to compare between the different sides and severities, using independent and paired tests, respectively. The progression of asymmetry was assessed by changes in affected/contralateral ratios with age using multi-group comparisons. Two hundred and ten unilateral cases were studied. Generally, the affected ramus and body were significantly smaller than on the contralateral side. Linear measurements on the affected side were shorter in the severe group. Regarding affected/contralateral ratios, the body was less affected than the ramus. Progressively decreased affected/contralateral ratios of body length, dentate segment volume, and hemimandible volume were found. Asymmetry in mandibular ramus and body regions presents in hemifacial microsomia, which involves ramus more. A significant contribution to progressive asymmetry from the body suggests treatment focus in this region.